Patient Empowerment in terms of the Access to the Online Health Information from Patients’ and Doctors’ Perspective – Survey Results - Magdalena SOBON; Zygmunt WASKOWSKI (Communications of International Proceedings, 2021)
Among many uses of the Internet, patients enjoy an access to the free information about health. It affects the shape of the relationship between patients and doctors. The main research problem analysed in this article is patient empowerment. The article aims to establish the influence of the patient’s access to the online information on the patient empowerment and the patient-doctor relationship. The article presents the findings of a survey conducted on 300 patients and 100 doctors. The major conclusions are: (a) the access of patients to the online information about health fosters the development of the patient empowerment in terms of their self-awareness as well as the readiness for modifying their behaviour in the patient-doctor relationship, (b) the respondents display different degrees of the patient empowerment, in relation to their demographic characteristics, (c) the surveyed doctors observe the growing level of empowerment among their patients.
Keywords: Patient Empowerment; E-health; Information Asymmetry; Online Health Information